Abdurrahman Wahid's View of Pancasila as the State's Basis - Warno Warno (Trigin Publisher, 2021)
The development of Islam has indeed become an integral part of Indonesian history. The debate on the relationship between religion and power has become an interesting discourse among religious observers and academics. If religion is treated as a constructive tool, then by itself religion can be used as a means to control all policies carried out by the authorities. Even during the colonial period, religion was used as a means of carrying out the